2010
DOI: 10.1159/000321984
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 Prevalence in Alzheimer’s Disease Patients Varies across Global Populations: A Systematic Literature Review and Meta-Analysis

Abstract: Background: The Ε4 allele of apolipoprotein E (APOE) is associated with Alzheimer’s disease (AD). However, attributable risk due to APOE4 varies by region and by race/ethnicity. Methods: A literature review and meta-analysis were conducted to estimate the prevalence of APOE4 by geographic area among AD patients. Results: Although estimates varied significantly by study design and case definition, AD patients recruited in Asian and southern European/Mediterranean communities seemed to have significantly lower E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 40 publications
11
86
3
7
Order By: Relevance
“…The polymorphism of APOE is considered as a definite risk factor for AD with ε4 allele (APOE4) showing strong association with the disease, but the estimated risk attributable to APOE4 varies in different populations depending on the frequency of this allele in a particular population [55]. The protein coded by APOE is apolipoprotein E which is involved in cholesterol transport in the periphery as well as cholesterol trafficking within the brain, and APOE genotype and serum total cholesterol interaction has been suggested in AD progression [56].…”
Section: Metabolic Risk Factors Of Ad: Present Statusmentioning
confidence: 99%
“…The polymorphism of APOE is considered as a definite risk factor for AD with ε4 allele (APOE4) showing strong association with the disease, but the estimated risk attributable to APOE4 varies in different populations depending on the frequency of this allele in a particular population [55]. The protein coded by APOE is apolipoprotein E which is involved in cholesterol transport in the periphery as well as cholesterol trafficking within the brain, and APOE genotype and serum total cholesterol interaction has been suggested in AD progression [56].…”
Section: Metabolic Risk Factors Of Ad: Present Statusmentioning
confidence: 99%
“…In a recent review and meta-analysis, E4 has been shown to be associated with about 65 to 75 percent of cases of non-Mendelian-inherited AD and up to 20 percent of all dementias (Crean et al, 2011). The meta-analysis found that 39 percent of AD patients from Asian countries carried the APOE4 allele, as did 43 percent of patients from southern Europe and the Mediterranean, 54 percent from central Europe, 59 percent from North America, and 64 percent from northern Europe.…”
Section: Geneticsmentioning
confidence: 99%
“…Having one or two E4 alleles or forms of the APOE gene is a major predictor of AD, although the evidence is somewhat inconsistent for African Americans (Chin et al, 2011;Crean et al, 2011;Graff-Radford et al, 2002;Logue et al, 2011;Tang et al, 1996). The E4 allele is associated with increased risk of AD among African Americans, but not among Yoruba (Hendrie et al, 2006).…”
Section: Geneticsmentioning
confidence: 99%
“…За наявності однієї алелі ε4 50 % жінок і чоловіків ризикують захво-ріти до 87 років [10]. Більш докладний метааналіз досліджень показав, що серед пацієнтів різної ра-сово-територіальної належності з ХА азіати і жи-телі Середземномор'я значно рідше були носіями ε4 (37 та 43 % відповідно), ніж хворі європеоїдного населення Північної Америки і Північної Європи (58 і 64 % відповідно; відмінності вірогідні між усі-ма групами; p < 0,05) [13].…”
Section: ключові слова: фібриляція передсердь; когнітивні порушення; unclassified